Analysis of Certificate Checking Activities in the Context of Registration of Transfer of Rights Due to Legal Events at the South Tangerang City Land Office - Maharani Cantika Sulaiman; Ariawan Gunadi (Syntax Corporation Indonesia, 2024)
This article aims to find out how land registration activities are carried out by the Government for the benefit of the people in order to guarantee legal certainty in the land sector. The problem focuses on the land rights registration system, the recording of which describes a detailed summary regarding the occurrence of property ownership and changes thereto, or other transactions that affect a property right. In order to approach this problem, theoretical references from several sources are used, including (1) legal protection theory; (2) theory of legal certainty. Data is collected through several sources such as interviews, observation results, events or test results of objects or documents in the form of books, journals, notes or other archives that are related and analyzed qualitatively. This study concludes that based on the urgency of the problem, the system for checking and registering land title certificates is carried out using an electronic system. The certificate check is carried out by the PPAT before the deed is made which is the basis for the legal act of transferring/assigning land rights. PPAT has the authority to check, copy, validate and register land title certificates as regulated in UUPA PP No. 24 of 1997 and PP no. 37 of 1998. The output of this system is in the form of printed documents in electronic form. In this case, the electronic document referred to is an electronic certificate or e-certificate.